Employee image in social media as a promotion tool / Harry Ray Usah - Usah, Harry Ray (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
In this modern day, there are quantitative or a lot of companies and brand that are deal with this modern market, by that they need to find out a new way and style in promoting their business activities. Other than promoting method they need to find out the most effective promoting style in the way to ensure that the products are really known to others and the details are very clear to be known by the user. The browsing algorithms are always changing in favor of personal accounts and this making the online browsing traffic to be packed and this it were necessarily to make a fee for a single post so that subscribers can view the products that they want without any disturbance such as advertisement that employee nowadays are being used as one of the communication and advertisement method in social media, by that employee are also can earn something such as pay for become the company model and in the same time they can promote themselves and can use that platform in the way to make their own business as they have been known by others while they promoting their company business activity in social media platform.